Photchananukrom khamphong - `Uthai Chaiyanon (Krung Thep : Samnakphim Nam Fon, 1997)
Thai language dictionary of synonyms.
In Thai.
Keywords: Thai language -- Dictionaries; Thai language -- Synonyms and antonyms